Proceeding of the 4th Libyan Conference on Medical and Pharmaceutical Sciences: ORGANIZED BY. Center of Scientific Research and International Cooperation - University of Tripoli Alahlia - Ahmed Atia1 and Nagib Elmarzugi2,3, (AlQalam Journal of Medical and Applied Sciences, 2020)
Gathering Notice of the Fourth Libyan Conference on Medical and Pharmaceutical Sciences. From the successful completion of the series of Libyan conference on medical and pharmaceutical sciences, we are delighted to welcome you to the fourth Libyan Conference of Medical and pharmaceutical sciences (4th LCMPS 2020). The congress is scheduled to take place in the city of Janzur, Libya, on November 14, 2020. This conference will deliver you with research experience and enormous thoughts. The theme of the 4th LCMPS 2020 is to set up relocate research to help individuals recognize how medical practices have advanced and established in recent years. While medication and treatment are crucial for helping and supporting individuals once they become sick, increase universal wealth adds to reducing the clarifications for sick prosperity and intensifying people's prosperity and wealth. 4th LCMPS 2020 online meeting will be operated with organizers with many proficient attributes of high quality, and the zooming techniques will allow conference speakers and attendees opportunities to involve in collective efforts while learning further about some of the up-to-date inclinations and research practices applied to report influences relative to the scope of the conference. The online summit has extended universal reaching out demand to call for speakers and attendees from many countries around the world, who have a prospect to attend the outcomes of valued research attempts reported by attending experts, speakers, operators, physicians and other professionals working in medical and pharmaceutical fields. Online events in medical sciences have a worldwide extension scope throughout the world. Such these gathering come up with suggestions to extend the best prospect for the academicians about cooperative efforts to present their inspection, and exchange professionals, displaying their objects, directions and networking. The reasonable gathering integrates oral and publication overviews, as well as workshops from the experts working in the field of medical and pharmaceutical sciences.